2018
DOI: 10.1097/md.0000000000010081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the McGrath videolaryngoscope and the Macintosh laryngoscope for double lumen endobronchial tube intubation in patients with manual in-line stabilization

Abstract: Background:Double lumen endobronchial tube (DLT) intubation is commonly used for one-lung ventilation in thoracic surgery. However, because of its large size and shape, it is difficult to perform intubation compared with a single lumen tube. The aim of this randomized controlled trial was to determine whether the McGrath videolaryngoscope has any advantage over the direct Macintosh laryngoscope for DLT intubation in patients with a simulated difficult airway.Methods:Forty-four patients (19–60 years of age); sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…Not only SV but also the other videoscopes showed better success rates than Mc. The results were consistent with the previous studies on DLT intubation [ 1 , 8 , 17 , 18 , 20 , 25 , 26 , 29 , 30 , 32 , 36 , 37 ]. However, the best choices differed according to the indicators.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Not only SV but also the other videoscopes showed better success rates than Mc. The results were consistent with the previous studies on DLT intubation [ 1 , 8 , 17 , 18 , 20 , 25 , 26 , 29 , 30 , 32 , 36 , 37 ]. However, the best choices differed according to the indicators.…”
Section: Discussionsupporting
confidence: 93%
“…For randomization, all of the 23 studies in our SR reported that the study was randomized; 20 of them (87%) reported that the method of random sequence generation was applied, whereas the other three studies (13%) did not provide adequate information [ 19 , 24 , 25 ]. The allocation concealment was adequately reported in 18 studies, four studies reported it inadequately [ 1 , 18 – 20 ], and one study checked as high risk [ 26 ]. For blinding, given that different devices were used in almost all RCT studies, all studies (100%) were evaluated as high risk in blinding of participants and personnel to the intervention of the studies (performance bias).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations